Optimalisasi Guru Ngaji Melalui Pembekalan Metode An-Nahdiyah Dalam Pembelajaran Al-Quran Di Madrasah Diniyah Al-Mujahidin Desa Bedrug - Neti Setiowati; Teguh Ansori; Suad Fikriawan (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The An-Nahdliyah method is a method of learning the Koran that places more emphasis on the suitability and regularity of reading with the beat of murattal footnotes. The advantage of this method is that with the help of tapping with a stick, each reading will be rhythmic, when we learn the early stages of the Koran with this method, we will not feel bored because the needs of both the right and left brain are met. In Bedrug Village, especially Dukuh Krajan, there is a Madrasah Diniyah Takmiliyah Awwaliyah called Madrasah Diniyah Al-Mujahidin which in the process of learning the Qur'an uses the media in the form of An-Nahdliyah volumes, however the method used is not the An-Nahdliyah method. By using the ABCD approach through participant observation methods and also interviews. The results of this study are that there are four stages carried out in the implementation of the An-Nahdliyah method training program, namely planning, socialization, implementation and also evaluation. From this activity, it is hoped that the teacher of the Koran will be able to apply the An-Nahdliyah method according to the procedure